2014
DOI: 10.1038/npp.2014.155
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil Effects on Middle-Frequency Oscillatory Power During Rule Selection in Schizophrenia

Abstract: Control-related cognitive processes such as rule selection are associated with cortical oscillations in the theta, alpha and, beta ranges, and modulated by catecholamine neurotransmission. Thus, a potential strategy for improving cognitive control deficits in schizophrenia would be to use pro-catecholamine pharmacological agents to augment these control-related oscillations. In a double-blind, placebo-controlled (within-subjects) study, we tested the effects of adjunctive single-dose modafinil 200 mg on rule-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…We tested this possibility with modafinil, a dopamine reuptake inhibitor that has been shown to increase extracellular levels of dopamine [22]. Based on a large literature [42,43], we had predicted that modafinil would dosedependently increase several signals, including N200, ERN, and frontal theta power. Surprisingly, none of these signals were modulated with modafinil in either species, though we observed a trend in stimulus-locked theta power in rats (p = 0.08) that may bear out in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…We tested this possibility with modafinil, a dopamine reuptake inhibitor that has been shown to increase extracellular levels of dopamine [22]. Based on a large literature [42,43], we had predicted that modafinil would dosedependently increase several signals, including N200, ERN, and frontal theta power. Surprisingly, none of these signals were modulated with modafinil in either species, though we observed a trend in stimulus-locked theta power in rats (p = 0.08) that may bear out in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using modafinil on memory deficits in schizophrenic patients are quite promising and improvement of short-term verbal memory, verbal WM performance, spatial WM errors (WMEs) and strategy use is furthermore observed in schizophrenics ( Turner et al, 2004a , b ; Scoriels et al, 2012 ). Minzenberg et al (2014) studied modafinil effects in schizophrenia and observed improvement of rule selection and representation. Moreover, modafinil was studied in healthy volunteers and significantly enhanced performance in trials of cognition such as WM, cognitive flexibility, and planning ( Muller et al, 2004 ; Turner et al, 2004a , b ; Finke et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action underlying this effect remains to be determined however. The pro-cognitive effects of modafinil may arise from its ability to facilitate middle frequency cortical oscillations (theta, alpha, beta) acutely (Minzenberg et al, 2014a, 2014b), or higher frequency cognitive-control related activity (gamma) with sustained treatment (Minzenberg et al, 2016). Further, McKenna and colleagues (McKenna et al, 2013) identified numerous regions underlying 5C-CPT performance using fMRI.…”
Section: Discussionmentioning
confidence: 99%